STRATEGI PEMASARAN PRODUK HALAL DALAM MEMASUKI PASAR GLOBAL - Imron Natsir; Kherayani Nur; Titik Purwati; Seno Lamsir; Eva Yuniarti Utami (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to determine the marketing strategy of halal products in entering the global market. This research approach collects data through literature studies, which involve reading literature from various sources including books, reports, articles, and journals using qualitative and deductive approaches. The findings in this study are that there are several stages in entering the global market, including no foreign marketing, infrequent foreign marketing, regular foreign marketing, and global marketing operations. In addition, there are also steps in entering the global market, namely market segmentation, global marketing research process, and strategy selection. There are several marketing strategies for halal products in entering the global market, namely product strategy, pricing strategy, distribution strategy, promotion strategy, responsive and adaptive global branding strategy, compliance strategy with international regulations, and international collaboration and partnership strategy.